STUDY CASE: THE OVEREXTENSION AND THE UNDEREXTENSION OF TWO YEARS OLD CHILDREN - ACHMAD FAIZIN; MAS DARUL IHSAN (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2017)
This research especially about study case related with the overextension and the underextension of two years old children in thier conversation in daily life. This research concerned in error correction and explicit teaching of rules in language acquisition. During the period of early lexical acquition, children usually experience the extensional error phenomenon. As the result, the researcher described all of the further explanation about the words that undergo the overextension phenomenon based on the visual features in table below.